Impact of Regular Exercise and Attempted Weight Loss on Quality of Life among Adults with and without Type 2 Diabetes Mellitus. (23rd September 2010) - Green, Andrew J.; Fox, Kathleen M.; Grandy, Susan
Abstract : Objective . To examine the association between exercising regularly and trying to lose weight, and quality of life among individuals with and without type 2 diabetes mellitus (T2DM). Methods . Respondents to the US SHIELD baseline survey reported whether they had tried to lose weight during the previous 12 months and whether they exercised regularly for >6 months. Respondents completed the SF-12 quality-of-life survey one year later. Differences between T2DM respondents (n = 2419 ) and respondents with no diabetes (n = 6750 ) were tested using t -tests and linear regression models adjusting for demographics, body mass index (BMI), and diabetes status. Results . After adjustment, exercising regularly was significantly associated with higher subsequent physical and mental component scores (P < .001 ). After adjustment, trying to lose weight was not associated with higher physical component scores (P = .87 ), but was associated with higher mental component scores (P = .01 ). Conclusion . Respondents who reported exercising regularly had significantly better physical and mental quality of life, compared with respondents who did not exercise regularly. Despite exercising regularly, respondents with T2DM had significantly worse quality of life, compared with respondents without diabetes who exercised regularly.